Better links for subscribers? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Also from Nigeria, in Ado-Etiki, Pastor Emmanuel Akindele asks us to 'produce a register of subscribers, to increase information exchange about development opportunities.'Nice idea Pastor, but a bit impractical since it would be a book with one...